Manufacturing method and application of alloy component

Through SLM technology, the nickel-titanium copper alloy powder is laser melted, which solves the problems of increased brittleness and poor processing performance of Ti-Ni-Cu alloy during processing, and realizes the manufacturing of high-performance damping materials for nickel-titanium copper alloy components , suitable for aerospace and military industries.

CN119187595APending Publication Date: 2024-12-27CHINA UNIV OF PETROLEUM (BEIJING)
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411123501.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-15
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The binary Ti-Ni-Cu alloy has problems of increased brittleness and poor processing performance during processing, making it difficult to create complex configurations, limiting its application as a high-performance damping material.

Method used

The SLM technology is used to perform the first laser melting treatment and the second laser melting treatment on the Ni-Ti-Ti-Copper alloy powder of Ti50Ni50-xCux (7.5≤x≤25), and the alloy member with excellent compression fracture strength and damping performance is formed by controlling the process parameters. This avoids complex processing processes such as mold development, casting, and forging.

Benefits of technology

It has achieved high molding accuracy, good surface quality, few internal defects of nickel-titanium copper alloy components, excellent compression and fracture strength and damping performance, and is suitable for high-performance damping materials/device in the aerospace and military industries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119187595A_ABST
    Figure CN119187595A_ABST
Patent Text Reader

Abstract

The invention provides a manufacturing method and application of an alloy component, and the manufacturing method of the alloy component comprises the following steps that (1) nickel-titanium-copper alloy powder is preset to form a to-be-treated layer, the chemical composition of the nickel-titanium-copper alloy powder is Ti50Ni50-xCux, and x is larger than or equal to 7.5 and smaller than or equal to 25; (2) first laser melting treatment and second laser melting treatment are sequentially carried out on the to-be-treated layer according to printing process parameters, the first laser melting treatment is in a strip rotating scanning mode, and a target layer is formed; and (3) the step (1) to the step (2) are repeatedly executed, and the nickel-titanium-copper alloy component is formed. The nickel-titanium-copper alloy component manufactured by the manufacturing method has excellent compression fracture strength and compression fracture strain, and also has relatively high damping performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of shape memory alloys, and relates to a method for manufacturing an alloy component, and in particular to a method for manufacturing and application of an alloy component. Background Art

[0002] In the fields of aerospace, national defense, transportation, etc., the application of damping materials is crucial. They can effectively reduce vibration and noise to ensure the smooth operation and durability of instruments and equipment. Therefore, the design and manufacture of high-performance damping materials is one of the research hotspots in the field of materials science. Among them, the binary Ti-Ni shape memory alloy has good damping properties in the martensitic state, which is related to the presence of abundant and easily mobile twin interfaces inside its martensitic phase; and through research, it is found that adding an appropriate amount of Cu to the binary Ti-Ni alloy can change the phase transformation path of the alloy, form a lower twin shear value, make the migration of the twin interface easier, and further improve its damping properties. However, the addition of Cu leads to increased brittleness of Ti-Ni-Cu alloy, poor processing performance, and difficulty in manufacturing its complex configuration, which greatly limits the application of Ti-Ni-Cu alloy as a high-performance damping material. Summary of the invention

[0003] In view of the above-mentioned defects, the present invention provides a method for manufacturing an alloy component. The nickel-titanium-copper alloy component manufactured by the manufacturing method has excellent compressive fracture strength and compressive fracture strain, and also has high damping performance.

[0004] The present invention also provides an alloy component, which is prepared by the above manufacturing method and has excellent compression fracture strength, compression fracture strain and damping performance.

[0005] The present invention provides a method for manufacturing an alloy component, the manufacturing method comprising the following steps:

[0006] 1) Pre-setting nickel-titanium-copper alloy powder to form a layer to be treated, wherein the nickel-titanium-copper alloy powder comprises a chemical composition of Ti 50 Ni 50-x Cu x , where 7.5≤x≤25;

[0007] 2) performing a first laser melting process and a second laser melting process on the layer to be processed in sequence according to printing process parameters to form a target layer;

[0008] The first laser melting process is a strip rotation scanning mode, the first laser power is 60-150W, the first laser scanning speed is 200-1400mm / s, and the first laser scanning spacing is 50-110μm;

[0009] In the second laser melting process, the second laser power is 60-80W, the second laser scanning speed is 200-600mm / s, and the second laser scanning spacing is 50-90μm;

[0010] 3) Repeat steps 1) to 2) to form a nickel-titanium-copper alloy component.

[0011] Furthermore, in the first laser melting process, the first laser power is 60-73W, and the first laser scanning speed is 200-400mm / s;

[0012] And / or, in the second laser melting process, the second laser power is 60-70 W, and the second laser scanning speed is 200-300 mm / s.

[0013] Furthermore, step 3) also includes heat treating the nickel-titanium-copper alloy component at a temperature of 600-700° C. and a time of 30-60 min.

[0014] Further, the chamber pressure during the manufacturing process is 5-25 mbar;

[0015] And / or, the circulating wind speed during the manufacturing process is 1.5-2.0 m / s.

[0016] Furthermore, in step 1), the thickness of the layer to be treated is 20-40 μm;

[0017] And / or, in step 1), the particle size of the nickel-titanium-copper alloy powder is 15-53 μm.

[0018] Furthermore, in step 2), in the strip rotation scanning mode, the strip width is 3-8 mm, the layer-by-layer rotation angle is θ, 50°≤θ<90°, and θ cannot be divided by 360°.

[0019] Furthermore, in step 2), the spot diameter of the first laser melting process and / or the second laser melting process is 50-100 μm.

[0020] Further, the substrate temperature during the manufacturing process is 170-200°C;

[0021] And / or, the oxygen content during the manufacturing process is not higher than 300 ppm.

[0022] Furthermore, before step 1), the process also includes preheating the nickel-titanium-copper alloy powder, wherein the preheating temperature is 80-120° C. and the time is 6-10 hours.

[0023] The present invention also provides an alloy component, which is prepared by any of the above-mentioned methods for manufacturing the alloy component.

[0024] The method for manufacturing the alloy component of the present invention comprises: 50 Ni 50-x Cu x The nickel-titanium-copper alloy powder with a diameter of 7.5≤x≤25 is subjected to a first laser melting treatment and a second laser melting treatment in sequence, and the process parameters in the two laser melting treatments are controlled. It is possible to process alloy components with high molding accuracy, good surface quality and few internal defects without the need for complex processing such as mold development, casting, forging, rolling and welding. The alloy components have excellent compressive fracture strength and compressive fracture strain, and have high damping performance, and are suitable for the processing and manufacturing of high-performance damping materials / devices in the aerospace and military fields. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 A perspective schematic diagram of the process of the nickel-titanium-copper alloy component processing method of the present invention;

[0026] Figure 2 is an optical micrograph of the nickel-titanium-copper alloy component in Example 1 of the present invention;

[0027] Figure 3 is an optical micrograph of the nickel-titanium-copper alloy component in Example 6 of the present invention;

[0028] Figure 4 is a dynamic mechanical analysis (DMA) curve of the nickel-titanium-copper alloy component in Example 1 of the present invention during the heating process;

[0029] Figure 5 is a dynamic thermomechanical analysis (DMA) curve of the nickel-titanium-copper alloy component in Example 1 of the present invention during the cooling process;

[0030] Figure 6 is a dynamic thermomechanical analysis (DMA) curve of the nickel-titanium-copper alloy component in Example 6 of the present invention during the heating process;

[0031] Figure 7 is a dynamic mechanical analysis (DMA) curve of the nickel-titanium-copper alloy component in Example 6 of the present invention during the cooling process;

[0032] Figure 8 is the compression mechanics curve of the nickel-titanium-copper alloy component in Example 1 of the present invention;

[0033] Fig. 9 This is the compression mechanics curve of the nickel-titanium-copper alloy component in Example 6 of the present invention. DETAILED DESCRIPTION

[0034] In order to make the purpose, technical solutions and advantages of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] A first aspect of the present invention provides a method for manufacturing an alloy component, the manufacturing method comprising the following steps:

[0036] 1) Pre-setting nickel-titanium-copper alloy powder to form a layer to be treated, the nickel-titanium-copper alloy powder includes a chemical composition of Ti 50 Ni 50- x Cu x , where 7.5≤x≤25;

[0037] 2) performing a first laser melting process and a second laser melting process on the layer to be processed in sequence according to the printing process parameters to form a target layer;

[0038] The first laser melting process is a strip rotation scanning mode, the first laser power is 60-150W, the first laser scanning speed is 200-1400mm / s, and the first laser scanning spacing is 50-110μm;

[0039] In the second laser melting process, the second laser power is 60-80W, the second laser scanning speed is 200-600mm / s, and the second laser scanning interval is 50-90μm;

[0040] 3) Repeat steps 1) to 2) to form a nickel-titanium-copper alloy component.

[0041] The manufacturing method of the present invention is to use SLM technology to produce a 50 Ni 50-x Cu x A method for processing a nickel-titanium-copper alloy powder (7.5≤x≤25) to obtain a nickel-titanium-copper alloy component. The nickel-titanium-copper alloy powder can be a nickel-titanium-copper pre-alloyed powder or a mixed powder of nickel-titanium and copper. The present invention preferably uses a nickel-titanium-copper pre-alloyed powder. The execution subject of the method can use a conventional SLM metal printer currently in the art. The SLM metal printer achieves the above steps 1) to 3) by controlling the pre-set nickel-titanium alloy powder and melting and cooling the nickel-titanium alloy powder to obtain a nickel-titanium-copper alloy component.

[0042] Exemplarily, the SLM metal printer includes a storage unit, a presetting unit, a platform unit, and a laser unit, wherein the presetting unit is used to pre-lay the NiTi alloy powder stored in the storage unit on the platform surface to form a to-be-processed layer, and the laser unit is used to perform laser melting on the to-be-processed layer according to the printing process parameters to form a target layer. After each target layer is formed, the platform unit will drop a certain distance in the height direction, so that the next cycle including pre-setting the NiTi alloy powder to form the to-be-processed layer and laser melting to form the target layer can be performed, and this cycle is repeated for N cycles (N>1). When the N target layers are accumulated and superimposed layer by layer in the height direction, a nickel-titanium-copper alloy component is formed.

[0043] Specifically, in step 1), the chemical composition is Ti 50 Ni 50-x Cu x The nickel-titanium-copper alloy powder (7.5≤x≤25) is pre-placed and spread on the surface of the platform to form a layer to be processed.

[0044] In step 2), the first laser melting treatment is performed on the above-mentioned layer to be processed according to the printing parameters. The first laser melting treatment adopts a strip rotation scanning mode, and the power of the first laser melting treatment is controlled to be 60-150W, the scanning speed is 200-1400mm / s, and the scanning spacing is 50-110μm to obtain an initial target layer; when the first laser melting treatment is completed, the outer contour of the initial target layer is immediately subjected to a second laser melting treatment, and the power of the second laser melting treatment is controlled to be 60-80W, the scanning speed is 200-600mm / s, and the scanning spacing is 50-90μm to obtain a final target layer.

[0045] The printing process parameters here refer to the data obtained by slicing the desired three-dimensional model using slicing software and then converting the sliced ​​data using a data processor. The printing process parameters generally include information used to represent the shape of the desired nickel-titanium-copper alloy component. Therefore, the printing process parameters can control the scanning path of the laser source to perform laser melting on the layer to be processed in a targeted and routed manner, thereby obtaining the final target layer.

[0046] The present invention does not specifically limit the stripe width and rotation angle in the stripe rotation scanning mode.

[0047] Preferably, the second laser scan is performed 2-5 times.

[0048] The present invention does not specifically limit the scanning mode of the second laser melting process. For example, any one of a strip rotation scanning mode, an overall long straight line scanning mode, and a checkerboard scanning mode may be used.

[0049] In step 3), after forming a final target layer according to the above steps 1)-2), the above steps 1)-2) are repeated, that is, the to-be-treated layer is continuously formed on the surface of the previous final target layer, and the to-be-treated layer is sequentially subjected to the first laser melting treatment and the second laser melting treatment to form a new final target layer. Multiple final target layers are sequentially superimposed to form a nickel-titanium-copper alloy component. The shape of the nickel-titanium-copper alloy component is consistent with the shape of the desired three-dimensional model.

[0050] The manufacturing method of the alloy component in the present invention not only does not require complex processing processes such as mold development, casting, forging, rolling and welding, but also can process alloy components with high molding accuracy, good surface quality and few internal defects, effectively improving the compressive fracture strength, compressive fracture strain and damping performance of the nickel-titanium-copper alloy component. Based on this phenomenon, the inventor analyzed and believed that the reason may be: by sequentially performing the first laser melting treatment and the second laser melting treatment on the to-be-treated layer formed by the nickel-titanium-copper alloy powder of special chemical composition, and controlling the process parameters during the treatment process, the nickel-titanium-copper powder can be fully melted to ensure good overlap between the molten pools, improve the bonding strength within and between the layers, and effectively promote the escape of gas in the molten pool, reduce the porosity of the component, and further reduce the internal stress of the component during the molding process through the second laser melting treatment, so that the prepared nickel-titanium-copper alloy component has higher compressive fracture strength, compressive fracture strain and damping performance. Among them, the molten pool is the smallest basic unit in the processing and molding process.

[0051] In a specific embodiment, in the first laser melting process, the first laser power is 60-73W, and the first laser scanning speed is 200-400mm / s. When the first laser power and scanning speed in the first laser melting process are further within the aforementioned range, the nickel-titanium-copper powder can be fully melted, significantly enhancing the metallurgical bonding effect within and between layers, and effectively promoting the escape of gas in the molten pool, further reducing the porosity of the alloy component, and making the nickel-titanium-copper alloy component have higher molding quality and mechanical properties.

[0052] Exemplarily, the first laser power is 60W, 62W, 64W, 66W, 68W, 70W, 72W or 73W; the first laser scanning speed is 200mm / s, 220mm / s, 240mm / s, 260mm / s, 280mm / s, 300mm / s, 320mm / s, 340mm / s, 360mm / s, 380mm / s or 400mm / s.

[0053] In a specific embodiment, in the second laser melting process, the second laser power is 60-70W, and the second laser scanning speed is 200-300mm / s. When the second laser power and the scanning speed in the second laser melting process are further within the aforementioned range, the molding quality and dimensional accuracy of the component surface can be further improved, while reducing the internal stress and improving the interlayer bonding strength, so that the ductility and damping performance of the component are further improved.

[0054] Exemplarily, the second laser power is 60 W, 61 W, 62 W, ​​63 W, 64 W, 65 W, 66 W, 67 W, 68 W, 69 W or 70 W; the second laser scanning speed is 200 mm / s, 210 mm / s, 220 mm / s, 230 mm / s, 240 mm / s, 250 mm / s, 260 mm / s, 270 mm / s, 280 mm / s, 290 mm / s or 300 mm / s.

[0055] In a specific embodiment, step 3) further includes heat treating the nickel-titanium-copper alloy component at a temperature of 600-700° C. for 30-60 minutes. When the finally formed nickel-titanium-copper alloy component is heat treated at a specific temperature for a certain period of time, the internal stress in the alloy component can be effectively eliminated, and its ductility can be improved, thereby further improving the compression fracture strain and damping performance.

[0056] Exemplarily, the temperature of the heat treatment is 600°C, 610°C, 620°C, 630°C, 640°C, 650°C, 660°C, 670°C, 680°C, 690°C or 700°C; the time of the heat treatment is 30 min, 35 min, 40 min, 45 min, 50 min, 55 min or 60 min.

[0057] In a specific embodiment, the chamber pressure during the manufacturing process is 5-25 mbar. When the chamber pressure is within the aforementioned range, the molten pool can be made more stable, which is conducive to the diffusion of the molten pool and the escape of gas, and the width (dimension in the transverse direction) and depth (dimension in the longitudinal direction) of the molten pool are more appropriate, thereby making the organizational properties of the formed parts uniform, improving the forming quality of the nickel-titanium-copper alloy components, and making them have better compression fracture strength, compression fracture strain and damping performance.

[0058] Exemplarily, the cabin pressure is 5 mbar, 7 mbar, 9 mbar, 11 mbar, 13 mbar, 15 mbar, 17 mbar, 19 mbar, 21 mbar, 23 mbar or 25 mbar.

[0059] In a specific embodiment, the circulating wind speed during the manufacturing process is 1.5-2.0 m / s. Within this range, the circulating wind speed is more suitable, which can effectively reduce the internal inclusion defects in the nickel-titanium-copper alloy component, thereby further improving the compression fracture strength, compression fracture strain and damping performance of the alloy component.

[0060] Exemplarily, the circulation wind speed is 1.5 m / s, 1.6 m / s, 1.7 m / s, 1.8 m / s, 1.9 m / s or 2.0 m / s.

[0061] In a specific embodiment, in step 1), the thickness of the layer to be treated is 20-40 μm. Within this range, it can be ensured that the nickel-titanium-copper powder in the layer to be treated can receive sufficient laser energy, thereby achieving changes in metallurgical structure and further improving the mechanical properties and damping properties of the component.

[0062] Exemplarily, the thickness of the layer to be treated is 20 μm, 22 μm, 24 μm, 26 μm, 28 μm, 30 μm, 32 μm, 34 μm, 36 μm, 38 μm or 40 μm.

[0063] In a specific embodiment, in step 1), the particle size of the nickel-titanium-copper alloy powder is 15-53 μm. Within this range, it is beneficial to further ensure that the nickel-titanium-copper powder is completely melted under the action of the laser, thereby improving the molding quality and mechanical properties of the component.

[0064] Illustratively, the particle size of the nickel-titanium-copper alloy powder is 15 μm, 19 μm, 23 μm, 27 μm, 31 μm, 35 μm, 39 μm, 43 μm, 47 μm, 51 μm or 53 μm.

[0065] In a specific implementation, in step 2), in the strip rotation scanning mode, the strip width is 3-8 mm, the layer-by-layer rotation angle is θ, 50°≤θ<90°, and θ cannot be divided by 360°.

[0066] Among them, the strip mode is to divide the layer to be processed into several strip areas, and then laser scan each strip area according to the printing process parameters, and the width of each strip area is the strip width. Figure 1 Schematic diagram of the process of the nickel-titanium-copper alloy component processing method of the present invention. Figure 1As shown, during the processing, M is the intermediate state of the nickel-titanium-copper alloy part formed by stacking the mth final target layer to the nth final target layer in sequence, and the (n+1)th final target layer a, the (n+2)th final target layer b and the (n+3)th final target layer c are stacked in sequence on the intermediate state. The first laser melting treatment in the processing method is a strip rotation scanning mode, wherein the (n+1)th to-be-processed layer a1 is divided into five strips, and the strip width of each strip is equal, that is, d. In the (n+1)th to-be-processed layer a1, the laser scans from the first strip to the fourth strip in the direction indicated by the arrow to obtain the (n+1)th initial target layer; and then the outer contour of the (n+1)th initial target layer is scanned by the second laser melting treatment to obtain the final target layer a. Secondly, the (n+2)th to-be-processed layer b1 is preset on the (n+1)th final target layer a according to the stacking direction, and the (n+2)th to-be-processed layer b1 is divided into seven strips. Next, the (n+3)th to-be-processed layer c1 is pre-placed on the (n+2)th final target layer b according to the stacking direction, and the (n+3)th to-be-processed layer c1 is divided into four strips. It should be noted that the (n+2)th to-be-processed layer b1 is rotated relative to the (n+1)th to-be-processed layer a1, and the rotation angle is θ1, and the (n+3)th to-be-processed layer c1 is rotated relative to the (n+2)th to-be-processed layer b1, and the rotation angle is θ2, and 50°≤θ1<90°, 50°≤θ2<90°, and it cannot be divided by 360°, for example, it can be 55°, 76°, 85, etc., which are not divisible by 360°.

[0067] The first laser melting treatment using the above-mentioned strip rotation scanning mode can cause the nickel-titanium-copper powder to undergo repeated melting and solidification during the forming process, which can not only significantly enhance the bonding effect of the nickel-titanium-copper powder between adjacent final target layers, but also ensure the full escape of gas in the molten pool, further improving the forming quality, mechanical properties and damping properties of the alloy components.

[0068] In a specific embodiment, the spot diameter of the first laser melting treatment and / or the second laser melting treatment is 50-100 μm. Within this range, the melting effect of nickel-titanium-copper powder under the action of laser can be better, avoiding the problem of excessive energy density caused by too small spot diameter, resulting in excessive melting of nickel-titanium-copper alloy powder, and excessive stress in the alloy component causing cracking. At the same time, it can also avoid the problem of too small energy density caused by too large spot diameter, resulting in incomplete melting of nickel-titanium-copper alloy powder, increasing the surface roughness of the alloy component, and reducing the forming accuracy. When the spot diameter of the first laser melting treatment and / or the second laser melting treatment is in the aforementioned range, the mechanical properties and forming accuracy of the alloy component can be further improved.

[0069] Exemplarily, the spot diameter is 50 μm, 55 μm, 60 μm, 65 μm, 70 μm, 75 μm, 80 μm, 85 μm, 90 μm, 95 μm or 100 μm.

[0070] In a specific embodiment, the substrate temperature during the manufacturing process is 170-200° C. By controlling the substrate temperature within the aforementioned range, the problem of excessive cooling speed and uneven thermal stress field, which may easily cause cracking due to the large temperature difference between the substrate and the molten pool, can be effectively avoided, further improving the forming quality and mechanical properties of the alloy component.

[0071] Illustratively, the substrate temperature is 170°C, 175°C, 180°C, 185°C, 190°C, 195°C, or 200°C.

[0072] In a specific embodiment, the oxygen content during the manufacturing process is not higher than 300 ppm. Within this range, the treated layer and the target layer can be protected to prevent the nickel-titanium-copper powder from undergoing oxidation reaction during the metallurgical process to form brittle oxides, which affects the ductility and damping properties of the alloy component.

[0073] For example, a protective gas, such as argon and / or nitrogen, may be introduced during the manufacturing process to control the oxygen content during the manufacturing process to be no higher than 300 ppm.

[0074] In a specific embodiment, before step 1), the nickel-titanium-copper alloy powder is also preheated at a temperature of 80-120° C. for 6-10 hours. By preheating the nickel-titanium-copper alloy powder, the nickel-titanium-copper powder can be made drier, the fluidity and spreadability of the powder can be improved, and the formed layer to be treated can be more uniform, so that the nickel-titanium-copper alloy powder can be more fully melted during the laser melting process, and the bonding effect of the powder in the final target layer can be significantly enhanced.

[0075] Exemplarily, the temperature of the preheat treatment is 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, 110°C, 115°C or 120°C; the time of the preheat treatment is 6h, 6.5h, 7h, 7.5h, 8h, 8.5h, 9h, 9.5h or 10h.

[0076] The present invention also provides an alloy component, which is prepared by the manufacturing method of the alloy component of the first aspect, so that the alloy component has excellent compressive fracture strength and compressive fracture strain, and also has high damping performance.

[0077] The manufacturing method of the present invention is described below through specific examples.

[0078] Example 1

[0079] 1) Ti with a particle size of 15-53 μm 50 Ni 50-x Cu x (x=15) alloy powder was preheated at 100℃ for 8h; a 3D model of a 10×10×6mm square sample was constructed, then sliced ​​and the printing process parameters were determined and input into the SLM machine control system;

[0080] 2) preheating the nickel-titanium substrate in the molding cavity to 185° C., and evenly spreading the preheated alloy powder on the nickel-titanium substrate to form a first treatment layer, and then introducing argon gas into the molding cavity to make the oxygen content inside the molding cavity not higher than 300 ppm;

[0081] 3) According to the first printing process parameters in the printing process parameters, the first layer to be processed is subjected to a first laser melting process to form a first initial target layer, and then the first initial target layer is subjected to a second laser melting process to form a first final target layer; subsequently, the powder cylinder containing the alloy powder automatically rises, and the nickel-titanium substrate automatically descends (the rising and descending heights are both the thickness of the second layer to be processed), and then the second layer to be processed is pre-placed on the first final target layer, and then according to the second printing process parameters in the printing process parameters, the second layer to be processed is subjected to a first laser melting process and a second laser melting process in sequence to form a second final target layer, and this cycle is repeated until the processing of the nickel-titanium-copper alloy component sample is completed;

[0082] Among them, the cabin pressure is 15mbar, the circulating wind speed is 1.8m / s; the power of the first laser melting treatment is 105W, the spot diameter is 75μm, the scanning speed is 800mm / s, the scanning spacing is 80μm, and the thickness of all layers to be treated is 30μm; the power of the second laser melting treatment is 70W, the spot diameter is 75μm, the scanning speed is 400mm / s, the scanning spacing is 70μm, and the number of scans is 2 times; the scanning mode selected for the first laser melting treatment is the strip rotation scanning mode, in which the strip width is 4mm and the layer-by-layer rotation angle is 70°; the scanning mode selected for the second laser melting treatment is the long straight line scanning mode;

[0083] 4) The nickel-titanium-copper alloy component sample processed as above was heat treated at 650° C. for 45 min to obtain the nickel-titanium-copper alloy component of this embodiment.

[0084] Example 2

[0085] 1) Ti with a particle size of 15-53 μm 50 Ni 50-x Cu xThe (x=10) alloy powder was preheated at 80°C for 10 h; a 3D model of a 10×10×6 mm square sample was constructed, which was then sliced ​​and the printing process parameters were determined and input into the SLM machine control system;

[0086] 2) preheating the nickel-titanium substrate in the molding cavity to 170° C., and evenly spreading the preheated alloy powder on the nickel-titanium substrate to form a first treatment layer, and then introducing argon gas into the molding cavity to make the oxygen content inside the molding cavity not higher than 300 ppm;

[0087] 3) According to the first printing process parameters in the printing process parameters, the first layer to be processed is subjected to a first laser melting process to form a first initial target layer, and then the first initial target layer is subjected to a second laser melting process to form a first final target layer; subsequently, the powder cylinder containing the alloy powder automatically rises, and the nickel-titanium substrate automatically descends (the rising and descending heights are both the thickness of the second layer to be processed), and then the second layer to be processed is pre-placed on the first final target layer, and then according to the second printing process parameters in the printing process parameters, the second layer to be processed is subjected to a first laser melting process and a second laser melting process in sequence to form a second final target layer, and this cycle is repeated until the processing of the nickel-titanium-copper alloy component sample is completed;

[0088] Among them, the cabin pressure is 5mbar, the circulating wind speed is 2m / s; the power of the first laser melting treatment is 65W, the spot diameter is 50μm, the scanning speed is 1400mm / s, the scanning spacing is 50μm, and the thickness of all layers to be treated is 20μm; the power of the second laser melting treatment is 60W, the spot diameter is 100μm, the scanning speed is 600mm / s, the scanning spacing is 50μm, and the number of scans is 2 times; the scanning mode selected for the first laser melting treatment is the strip rotation scanning mode, in which the strip width is 4mm and the layer-by-layer rotation angle is 50°; the scanning mode selected for the second laser melting treatment is the long straight line scanning mode;

[0089] 4) The nickel-titanium-copper alloy component sample processed as above was heat treated at 600° C. for 60 min to obtain the nickel-titanium-copper alloy component of this embodiment.

[0090] Example 3

[0091] 1) Preheating Ti50Ni50-xCux (x=15) alloy powder with a particle size of 15-53 μm at 90°C for 9 h; constructing a 3D model of a 10×10×6 mm square sample, then slicing it and determining the printing process parameters and inputting them into the SLM machine processing control system;

[0092] 2) preheating the nickel-titanium substrate in the molding cavity to 177° C., and evenly spreading the preheated alloy powder on the nickel-titanium substrate to form a first treatment layer, and then introducing argon gas into the molding cavity to make the oxygen content inside the molding cavity not higher than 300 ppm;

[0093] 3) According to the first printing process parameters in the printing process parameters, the first layer to be processed is subjected to a first laser melting process to form a first initial target layer, and then the first initial target layer is subjected to a second laser melting process to form a first final target layer; subsequently, the powder cylinder containing the alloy powder automatically rises, and the nickel-titanium substrate automatically descends (the rising and descending heights are both the thickness of the second layer to be processed), and then the second layer to be processed is pre-placed on the first final target layer, and then according to the second printing process parameters in the printing process parameters, the second layer to be processed is subjected to a first laser melting process and a second laser melting process in sequence to form a second final target layer, and this cycle is repeated until the processing of the nickel-titanium-copper alloy component sample is completed;

[0094] Among them, the cabin pressure is 10mbar, the circulating wind speed is 1.9m / s; the power of the first laser melting treatment is 80W, the spot diameter is 62μm, the scanning speed is 1100mm / s, the scanning spacing is 65μm, and the thickness of all layers to be treated is 25μm; the power of the second laser melting treatment is 65W, the spot diameter is 87μm, the scanning speed is 500mm / s, the scanning spacing is 60μm, and the number of scans is 2 times; the scanning mode selected for the first laser melting treatment is the strip rotation scanning mode, in which the strip width is 4mm and the layer-by-layer rotation angle is 61°; the scanning mode selected for the second laser melting treatment is the long straight line scanning mode;

[0095] 4) The nickel-titanium-copper alloy component sample processed as above was heat treated at 625° C. for 52 minutes to obtain the nickel-titanium-copper alloy component of this embodiment.

[0096] Example 4

[0097] 1) Ti with a particle size of 15-53 μm 50 Ni 50-x Cu x The (x=20) alloy powder was preheated at 110°C for 7h; a 3D model of a 10×10×6mm square sample was constructed, which was then sliced ​​and the printing process parameters were determined and input into the SLM machine control system;

[0098] 2) preheating the nickel-titanium substrate in the molding cavity to 192° C., and evenly spreading the preheated alloy powder on the nickel-titanium substrate to form a first treatment layer, and then introducing argon gas into the molding cavity to make the oxygen content inside the molding cavity not higher than 300 ppm;

[0099] 3) According to the first printing process parameters in the printing process parameters, the first layer to be processed is subjected to a first laser melting process to form a first initial target layer, and then the first initial target layer is subjected to a second laser melting process to form a first final target layer; subsequently, the powder cylinder containing the alloy powder automatically rises, and the nickel-titanium substrate automatically descends (the rising and descending heights are both the thickness of the second layer to be processed), and then the second layer to be processed is pre-placed on the first final target layer, and then according to the second printing process parameters in the printing process parameters, the second layer to be processed is subjected to a first laser melting process and a second laser melting process in sequence to form a second final target layer, and this cycle is repeated until the processing of the nickel-titanium-copper alloy component sample is completed;

[0100] Among them, the cabin pressure is 20mbar, the circulating wind speed is 1.6m / s; the power of the first laser melting treatment is 130W, the spot diameter is 87μm, the scanning speed is 500mm / s, the scanning spacing is 105μm, and the thickness of all layers to be treated is 35μm; the power of the second laser melting treatment is 75W, the spot diameter is 62μm, the scanning speed is 300mm / s, the scanning spacing is 80μm, and the number of scans is 2 times; the scanning mode selected for the first laser melting treatment is the strip rotation scanning mode, in which the strip width is 4mm and the layer-by-layer rotation angle is 81°; the scanning mode selected for the second laser melting treatment is the long straight line scanning mode;

[0101] 4) The nickel-titanium-copper alloy component sample processed as above was heat treated at 675° C. for 53 min to obtain the nickel-titanium-copper alloy component of this embodiment.

[0102] Example 5

[0103] 1) Ti with a particle size of 15-53 μm 50 Ni 50-x Cu x The (x=25) alloy powder was preheated at 120°C for 6 h; a 3D model of a 10×10×6 mm square sample was constructed, which was then sliced ​​and the printing process parameters were determined and input into the SLM machine control system;

[0104] 2) preheating the nickel-titanium substrate in the molding cavity to 200° C., and evenly spreading the preheated alloy powder on the nickel-titanium substrate to form a first treatment layer, and then introducing argon gas into the molding cavity to make the oxygen content inside the molding cavity not higher than 300 ppm;

[0105] 3) According to the first printing process parameters in the printing process parameters, the first layer to be processed is subjected to a first laser melting process to form a first initial target layer, and then the first initial target layer is subjected to a second laser melting process to form a first final target layer; subsequently, the powder cylinder containing the alloy powder automatically rises, and the nickel-titanium substrate automatically descends (the rising and descending heights are both the thickness of the second layer to be processed), and then the second layer to be processed is pre-placed on the first final target layer, and then according to the second printing process parameters in the printing process parameters, the second layer to be processed is subjected to a first laser melting process and a second laser melting process in sequence to form a second final target layer, and this cycle is repeated until the processing of the nickel-titanium-copper alloy component sample is completed;

[0106] Among them, the cabin pressure is 25mbar, the circulating wind speed is 1.5m / s; the power of the first laser melting treatment is 150W, the spot diameter is 100μm, the scanning speed is 200mm / s, the scanning spacing is 110μm, and the thickness of all layers to be treated is 40μm; the power of the second laser melting treatment is 80W, the spot diameter is 50μm, the scanning speed is 200mm / s, the scanning spacing is 90μm, and the number of scans is 2 times; the scanning mode selected for the first laser melting treatment is the strip rotation scanning mode, in which the strip width is 4mm and the layer-by-layer rotation angle is 89°; the scanning mode selected for the second laser melting treatment is the long straight line scanning mode;

[0107] 4) The nickel-titanium-copper alloy component sample processed as above was heat treated at 700° C. for 60 min to obtain the nickel-titanium-copper alloy component of this embodiment.

[0108] Example 6

[0109] The manufacturing method of the nickel-titanium-copper alloy component in this embodiment is basically the same as that in Example 1, except that, in step 3), the power of the first laser melting treatment is adjusted to 65 W, and the scanning speed is adjusted to 300 mm / s; the power of the second laser melting treatment is adjusted to 60 W, and the scanning speed is adjusted to 250 mm / s.

[0110] Example 7

[0111] The manufacturing method of the nickel-titanium-copper alloy component in this embodiment is basically the same as that in Embodiment 6, except that in step 3), the power of the first laser melting process is 75W.

[0112] Example 8

[0113] The manufacturing method of the nickel-titanium-copper alloy component in this embodiment is basically the same as that in Embodiment 6, except that in step 3), the scanning speed of the first laser melting process is 410 mm / s.

[0114] Example 9

[0115] The manufacturing method of the nickel-titanium-copper alloy component in this embodiment is basically the same as that in Embodiment 6, except that in step 3), the power of the second laser melting process is 72W.

[0116] Example 10

[0117] The manufacturing method of the nickel-titanium-copper alloy component in this embodiment is basically the same as that in Embodiment 6, except that in step 3), the scanning speed of the second laser melting process is 320 mm / s.

[0118] Embodiment 11

[0119] The manufacturing method of the nickel-titanium-copper alloy component in this embodiment is basically the same as that in Embodiment 1, except that step 4) is not included, that is, the processed nickel-titanium-copper alloy component sample is not subjected to heat treatment.

[0120] Example 12

[0121] The manufacturing method of the nickel-titanium-copper alloy component in this embodiment is basically the same as that in Embodiment 1, except that in step 4), the heat treatment temperature is adjusted to 500° C. and the heat treatment time is adjusted to 20 min.

[0122] Embodiment 13

[0123] The manufacturing method of the nickel-titanium-copper alloy component in this embodiment is basically the same as that in Embodiment 1, except that in step 4), the heat treatment temperature is adjusted to 800° C. and the heat treatment time is adjusted to 80 min.

[0124] Embodiment 14

[0125] The manufacturing method of the nickel-titanium-copper alloy component in this embodiment is basically the same as that in Embodiment 1, except that in step 4), the heat treatment temperature is adjusted to 500° C. and the heat treatment time is adjusted to 80 min.

[0126] Embodiment 15

[0127] The manufacturing method of the nickel-titanium-copper alloy component in this embodiment is basically the same as that in Embodiment 1, except that in step 4), the heat treatment temperature is adjusted to 800° C. and the heat treatment time is adjusted to 20 min.

[0128] Example 16

[0129] The manufacturing method of the nickel-titanium-copper alloy component in this embodiment is basically the same as that in Embodiment 1, except that in step 3), the cabin pressure is adjusted to 2 mbr.

[0130] Embodiment 17

[0131] The manufacturing method of the nickel-titanium-copper alloy component in this embodiment is basically the same as that in Embodiment 1, except that in step 3), the cabin pressure is adjusted to 35 mbr.

[0132] Embodiment 18

[0133] The manufacturing method of the nickel-titanium-copper alloy component in this embodiment is basically the same as that in Embodiment 1, except that in step 3), the circulating wind speed is adjusted to 2.6 m / s.

[0134] Embodiment 19

[0135] The manufacturing method of the nickel-titanium-copper alloy component in this embodiment is basically the same as that in Embodiment 1, except that in step 3), the circulating wind speed is adjusted to 0.9 m / s.

[0136] Embodiment 20

[0137] The manufacturing method of the nickel-titanium-copper alloy component in this embodiment is basically the same as that in Embodiment 1, except that in step 3), the thickness of the layer to be treated is adjusted to 50 μm.

[0138] Embodiment 21

[0139] The manufacturing method of the nickel-titanium-copper alloy component in this embodiment is basically the same as that in Embodiment 1, except that in step 1), the preheating treatment time is adjusted to 3 hours.

[0140] Comparative Example 1

[0141] The manufacturing method of the nickel-titanium-copper alloy component in this comparative example is basically the same as that in Example 1, except that in step 1), Ti 50 Ni 50-x Cu x x=5 in the alloy powder.

[0142] Comparative Example 2

[0143] The manufacturing method of the nickel-titanium-copper alloy component in this comparative example is basically the same as that in Example 1, except that in step 3), after the first laser melting treatment, the second laser melting treatment is not performed, and the pre-treatment layer is directly started for subsequent treatment.

[0144] Comparative Example 3

[0145] The manufacturing method of the nickel-titanium-copper alloy component in this comparative example is basically the same as that in Example 1, except that in step 3), the scanning speed of the first laser melting process is adjusted to 150 mm / s.

[0146] Comparative Example 4

[0147] The manufacturing method of the nickel-titanium-copper alloy component in this comparative example is basically the same as that in Example 1, except that in step 3), the scanning pitch of the first laser melting process is adjusted to 40 μm.

[0148] Comparative Example 5

[0149] The manufacturing method of the nickel-titanium-copper alloy component in this comparative example is basically the same as that in Example 1, except that in step 3), the scanning spacing of the first laser melting process is adjusted to 125 μm.

[0150] Comparative Example 6

[0151] The manufacturing method of the nickel-titanium-copper alloy component in this comparative example is basically the same as that in Example 1, except that in step 3), the power of the second laser melting treatment is adjusted to 50 W, the scanning speed is adjusted to 700 mm / s, and the scanning interval is adjusted to 100 μm.

[0152] Test example

[0153] 1. The nickel-titanium-copper alloy components in the above-mentioned Examples 1 and 6 were tested under an optical microscope. The test results are shown in Figure 2 and Figure 3 .

[0154] Figure 2 is an optical microscope photograph of the nickel-titanium-copper alloy component in Example 1. Figure 2 It can be seen that the component has no obvious defects such as pores and cracks at the microscopic level, and the molding quality is good.

[0155] Figure 3 is an optical microscope photograph of the nickel-titanium-copper alloy component in Example 6. Figure 3 It can be seen that the component has no obvious defects such as pores and cracks at the microscopic level, and the molding quality is good.

[0156] 2. Dynamic mechanical analysis (DMA) test was performed on the nickel-titanium-copper alloy components in Example 1 and Example 6. The DMA test parameters were set as follows:

[0157] The test fixture is a film stretching fixture; the cycle temperature range is -15 to 130°C, the heating rate and cooling rate are both 5°C / min; the preload is 5N; the dynamic force tracking is 125%; the amplitude range is 15-25μm; the test frequencies are 0.02Hz, 0.04Hz, 1Hz, 5Hz, 15Hz, 20Hz; the holding time is 5min. The test results are shown in Table 1 and Figure 4-Figure 7 .

[0158] Figure 4 is the dynamic mechanical analysis (DMA) curve of the nickel-titanium-copper alloy component in Example 1 during the heating process, Figure 4It can be seen that the nickel-titanium-copper alloy component has a relatively high damping performance below 40°C, wherein the tanδ of the alloy component is as high as 0.075.

[0159] Figure 5 is the dynamic mechanical analysis (DMA) curve of the nickel-titanium-copper alloy component in Example 1 during the cooling process, Figure 5 It can be seen that the nickel-titanium-copper alloy component has a relatively high damping performance below 40°C, wherein the tanδ of the alloy component is as high as 0.075.

[0160] Figure 6 is the dynamic mechanical analysis (DMA) curve of the nickel-titanium-copper alloy component in Example 6 during the heating process, Figure 6 It can be seen that the nickel-titanium-copper alloy component has a relatively high damping performance below 50°C, wherein the tanδ of the alloy component is as high as 0.084.

[0161] Figure 7 is the dynamic mechanical analysis (DMA) curve of the nickel-titanium-copper alloy component in Example 6 during the cooling process, Figure 7 It can be seen that the nickel-titanium-copper alloy component has a relatively high damping performance below 50°C, wherein the tanδ of the alloy component is as high as 0.084.

[0162] 3. Testing the mechanical properties of the nickel-titanium-copper alloy components prepared in the above embodiments and comparative examples comprises the following steps:

[0163] According to GB / T7314-2017 standard, the nickel-titanium-copper alloy components were subjected to compression tests to obtain the compression stress-strain curve. The compression fracture strength and compression fracture strain of the nickel-titanium-copper alloy components were obtained according to the compression stress-strain curve. The test results are shown in Table 1 and Figure 8 , Fig. 9 .

[0164] Figure 8 is the compression mechanics curve of the nickel-titanium-copper alloy component in Example 1, Figure 8 It can be seen that the room temperature compressive strength of the nickel-titanium-copper alloy component prepared in Example 1 can reach more than 1500 MPa, and the fracture strain can reach more than 22%.

[0165] Fig. 9 is the compression mechanics curve of the nickel-titanium-copper alloy component in Example 6, Fig. 9 It can be seen that the room temperature compressive strength of the nickel-titanium-copper alloy component prepared in Example 6 can reach more than 1500 MPa, and the fracture strain can reach more than 22%.

[0166] Table 1

[0167]

[0168]

[0169] From Table 1, we can see that:

[0170] The nickel-titanium-copper alloy components prepared in Examples 1 to 21 have high mechanical properties and damping properties. Specifically, the nickel-titanium-copper alloy component in Example 6 has a compressive fracture strength of up to 1542.49MPa, a compressive fracture strain of up to 22.92%, and a tanδ of up to 0.084; while the nickel-titanium-copper alloy components prepared in Comparative Examples 1 to 6 have a maximum compressive fracture strength of only 1287MPa, and correspondingly, a compressive fracture strain of only 13.9%, and a tanδ of only 0.050. It can be seen that the nickel-titanium-copper material laser additive processing method in the present invention can realize processing using nickel-titanium-copper alloy powder as raw material, and the obtained nickel-titanium-copper alloy parts have excellent mechanical strength and damping properties.

[0171] In addition, the mechanical strength and damping properties of the nickel-titanium-copper alloy parts can be further adjusted by adjusting the process parameters of the laser additive manufacturing method and / or the specific composition of the nickel-titanium-copper alloy powder. Therefore, the present invention has a wide range of application and can obtain nickel-titanium-copper alloy parts with different mechanical strengths and damping properties to meet different needs; or raw materials of different compositions can be used as processing objects and ultimately nickel-titanium-copper alloy parts that meet the needs can be obtained.

[0172] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for manufacturing an alloy component, characterized in that: The manufacturing method comprises the following steps: 1) Pre-setting nickel-titanium-copper alloy powder to form a layer to be treated, wherein the nickel-titanium-copper alloy powder comprises a chemical composition of Ti 50 Ni 50- x Cu x , where 7.5≤x≤25; 2) performing a first laser melting process and a second laser melting process on the layer to be processed in sequence according to printing process parameters to form a target layer; The first laser melting process is a strip rotation scanning mode, the first laser power is 60-150W, the first laser scanning speed is 200-1400mm / s, and the first laser scanning spacing is 50-110μm; In the second laser melting process, the second laser power is 60-80W, the second laser scanning speed is 200-600mm / s, and the second laser scanning interval is 50-90μm; 3) Repeat steps 1) to 2) to form a nickel-titanium-copper alloy component.

2. The method for manufacturing an alloy component according to claim 1, characterized in that: In the first laser melting process, the first laser power is 60-73W, and the first laser scanning speed is 200-400mm / s; And / or, in the second laser melting process, the second laser power is 60-70 W, and the second laser scanning speed is 200-300 mm / s.

3. The method for manufacturing an alloy member according to claim 1 or 2, characterized in that: Step 3) also includes heat treating the nickel-titanium-copper alloy component at a temperature of 600-700° C. for 30-60 minutes.

4. The method for manufacturing an alloy component according to any one of claims 1 to 3, characterized in that: The chamber pressure during the manufacturing process is 5-25 mbar; And / or, the circulating wind speed during the manufacturing process is 1.5-2.0 m / s.

5. The method for manufacturing an alloy component according to any one of claims 1 to 4, characterized in that: In step 1), the thickness of the layer to be treated is 20-40 μm; And / or, in step 1), the particle size of the nickel-titanium-copper alloy powder is 15-53 μm.

6. The method for manufacturing an alloy component according to any one of claims 1 to 5, characterized in that: In step 2), in the strip rotation scanning mode, the strip width is 3-8 mm, the layer-by-layer rotation angle is θ, 50°≤θ<90°, and θ cannot be divided by 360°.

7. The method for manufacturing an alloy component according to any one of claims 1 to 6, characterized in that: In step 2), the spot diameter of the first laser melting process and / or the second laser melting process is 50-100 μm.

8. The method for manufacturing an alloy component according to any one of claims 1 to 7, characterized in that: The substrate temperature during the manufacturing process is 170-200°C; And / or, the oxygen content during the manufacturing process is not higher than 300 ppm.

9. The method for manufacturing an alloy component according to any one of claims 1 to 8, characterized in that: Prior to step 1), the process also includes preheating the nickel-titanium-copper alloy powder at a temperature of 80-120° C. for 6-10 hours.

10. An alloy component, characterized in that: The alloy component is prepared by the manufacturing method of any one of claims 1 to 9.